PROCESS OF DISSOLVED AIR FLOTATION IN THE TREATMENT OF WASTE WATER PUMPING IN THE INDUSTRY OF FISH MEAL - Salas Colotta, G. (2003)
This paper experimentally studies the separation of pollutants in waste water from industry meal and fish oil, through a process of dissolved air flotation (DAF). The experimental results showed a removal of 60% SS, 98% and 66% BOD FOG.